INCIDENCE OF SPIRURID NEMATODE INFECTION IN RELATION TO THE WEIGHT, LENGTH AND SEX OF COLDWATER FISHES - KUMAR, ARUN; CHOPRA, A. K.; SINGH, H. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
The incidence of spirurid nematode infection was found to increase significantly (P<0.01) with an increase in weight and length of coldwater fishes; Schizothorax richardsonii, S. plagiostomus, Garra gotyla, and Crossocheilus latius. The older fishes had more incidence of infection. Further, the male fishes were found to be more susceptible to infection than the females.